2009
DOI: 10.29333/ejgm/82643
|View full text |Cite
|
Sign up to set email alerts
|

Is Medical Check-Up Useful for Physician among New University Students During Enrolling Time to University? a Survey of 640 New University Students

Abstract: Aim: The aim of this study is to investigate the health problems of the recently enrolled new university students in Celal Bayar (Spearman r=0.259, p=0.000). Headache was found higher in subjects with epilepsy than others (p= 0.020). Conclusion:Physicians of school based health centers, firstly, must understand students' health problems. This study emphasizes the importance of health screening of enrolling students in the registration time and the necessity of school based health centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The authors reported about 91% college students at the University of Minnesota had upper respiratory infections. A survey of new University students in Turkey revealed that headache, allergy, anemia and gastritis were the most frequent diseases (21).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported about 91% college students at the University of Minnesota had upper respiratory infections. A survey of new University students in Turkey revealed that headache, allergy, anemia and gastritis were the most frequent diseases (21).…”
Section: Discussionmentioning
confidence: 99%
“…These houses are public institutions where university students are highly exposed to respiratory diseases. Therefore, in these residential areas, to prevent symptomatic infections, individual measures are recommended (Mergen et al, 2009). Studies have shown that gender is one of the most important factors associated with chronic obstructive pulmonary disease (Varkey, 2004).…”
Section: Discussionmentioning
confidence: 99%